2018
DOI: 10.1111/eos.12584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methacrylated chitosan incorporated in experimental composite and adhesive on mechanical properties and biofilm formation

Abstract: The lifespan of a resin‐based restoration is limited, with the main reason for failure being secondary caries. Biofilm formation at the tooth–material interface is a necessary etiological agent for caries development. Dental materials with antimicrobial properties may reduce formation of biofilm and thus increase the longevity of restorations. This study aimed to investigate the effect of methacrylated chitosan (CH‐MA), incorporated into the polymeric network of an experimental dental composite and adhesive, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…In the present study, although no statistical difference was found in the color stability in the chitosan-modified material compared with that in the control group, a higher color stability was found in the modified material, especially after the storage in distilled water and red-wine solutions. The methacrylation of low-molecular-weight chitosan and its incorporation into the polymer network of composites and adhesives have produced stable materials after storage in water, 32 which could explain the results of the present research.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, although no statistical difference was found in the color stability in the chitosan-modified material compared with that in the control group, a higher color stability was found in the modified material, especially after the storage in distilled water and red-wine solutions. The methacrylation of low-molecular-weight chitosan and its incorporation into the polymer network of composites and adhesives have produced stable materials after storage in water, 32 which could explain the results of the present research.…”
Section: Discussionsupporting
confidence: 70%
“…Chitosan itself also has antimicrobial activities at acidic pH [221]. It could reduce biofilm formation in in vitro studies when being incorporated into resin-based composite materials [222]. Some studies also tried to successfully disrupt biofilm formation by impairing adhesion between Streptococci and Porphyromonas [223,224].…”
Section: Functionalization Of Dental Materials With Antimicrobial Activitiesmentioning
confidence: 99%
“…There have been many attempts to develop new bio-stable and antidegradation immobilized antimicrobial agents [ 98 , 99 , 100 , 101 ]. The nanoassemblies formed by Fmoc-pentafluoro-l-phenylalanine-OH (Fmoc-F5-Phe) have been functionally incorporated within resin-based composites.…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
“…Several studies have modified antimicrobial agents, for example, by connecting them to a methacrylate monomer, so that they can be added to the crosslinked network of the resin composite [ 99 , 100 ]. A triclosan methacrylate (TM) monomer was developed and incorporated into an experimental resin composite.…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
See 1 more Smart Citation